Improving Teacher Work Discipline in Madrasah Through Charismatic Leadership - Muali, Chusnul; Ridwan, Ridwan; Huda, Huda; Akbar, Abdul Rozaq (JURNAL AL-TANZIM, 2022)
This paper describes the charismatic principal in improving teacher work discipline in pesantren-based madrasah. Teacher work discipline is quite essential because departing from the work discipline of the teacher, and it can also be seen how the process and quality in the institution. This research takes place at Madrasah Aliyah Nurul Jadid Paiton, which incidentally is a pesantren-based madrasah. This study aims to contribute ideas guidelines for madrasah principals in improving work discipline. This research uses a qualitative case study approach. The informants included the head of the madrasah, deputy head, organizational builder, waka curriculum, waka student, teacher, and one student of Madrasah Aliyah Nurul Jadid Paiton, through purposive sampling. The data analysis uses Miles and Huberman's concepts, namely data reduction, data presentation, and conclusions or data verification. The research results obtained include; 1) A strong personality aura that is respected as one that affects the discipline of the teacher's work; 2) Being responsible for the main tasks and positions becomes the teacher's consideration for discipline; 3) Visionary in compiling and innovating about the future direction of the madrasah; and 4) Becoming an example in all aspects for their subordinates in the discipline.